Strengthening the Business Management of Cattle Waste Compost Fertilizer in Tanjung Karang, Malaysia: Pengabdian - Supiah Ningsih; Jufrizen; Muhammad Irfan Nasution; Sabrina; Nor Bakhriah Sarbani (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
participatory and empowerment-based method consisting of preliminary assessment, training, mentoring, and evaluation. The activities included business management training, assistance in simple bookkeeping, strengthening of production organization, improvement of packaging and labeling awareness, and introduction to basic marketing strategies. The results showed that the PKM contributed to improving participants’ understanding of business management, enhancing production organization, introducing simple financial recording practices, increasing awareness of product packaging and branding, and broadening marketing perspectives. The program also encouraged the community to view cattle waste not merely as a disposal problem but as a valuable local economic resource. Overall, this PKM demonstrates that strengthening managerial capacity is essential for transforming community-based composting activities into more sustainable and competitive local enterprises. The experience also provides a practical model for integrating environmental management, entrepreneurship, and rural community empowerment